Chemically tuned light source with an optical pump - Włodarski, Jakub; Chychłowski, Miłosz (Photonics Letters of Poland, 2021)
This article presents the latest results of rhodamine B and fluorescein solutions emissions at different weight concentrations. The shift of emitted central peak wavelength is observed to change in weight concentrations of the active material in samples. By using only two active materials photoluminescence at desired wavelength form range 524nm – 660nm can be achieved. All samples were excited sequentially by a laser source and two blue light-emitting diodes without significant changes in the emitted spectra. Full Text: PDF References J. R. Lakowicz, Principles of Fluorescence Spectroscopy. Springer Science & Business Media, Pages 1-6, (2013). CrossRef R. Sjöback, J. Nygren, M. Kubista, "Absorption and fluorescence properties of fluorescein", Spectrochimica Acta Part A: Molecular Spectroscopy, Volume 51, L7-L21, (1995) CrossRef M. F. Al-Kadhemy, I. F. Alsharuee, A. A. D. Al-Zuky, "Analysis of the effect of the concentration of rhodamine B in ethanol on the fluorescence spectrum using the ’Gauss Mod’function", Journal of Physical Science, 22(2), 77-86, (2011). DirectLink F. M. Zehentbauer, et al., "Fluorescence spectroscopy of Rhodamine 6G: Concentration and solvent effects", Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 121, 147-151, (2014) CrossRef M. F. H. Al-Kadhemy, A. A. D. Al-Zuky, H. F. Daear, "Theoretical Model for the Effect of Temperature on the Fluorescence Spectrum of Laser Dye (Rh6G) in Acetone", International Letters of Chemistry, Physics and Astronomy, 19, (2014). CrossRef A. H.Al-Hamdani, S. M. Jasim, E. M. Abbas, D. A. Hassan, M. M. Jaber, "Spectral Properties of Hybrid of Rhodamine (6G) Dyes Doped Epoxy Resin Dissolved in Chloroform", Baghdad Science Journal, 16(3 Supplement), 764-769, (2019). http://dx.doi.org/10.21123/bsj.2019.16.3(Suppl.).0764 CrossRef Mengwei Liu, et al., "Instrument response standard in time-resolved fluorescence spectroscopy at visible wavelength: quenched fluorescein sodium", Applied spectroscopy, 68.5: 577-583, (2014) CrossRef C. Bojarski, G. Żurkowska, J. Tyrzyk, "The Concentrational Changes of the Fluorescence Decay Time of Rhodamine B in Ethanol", Zeitschrift für Naturforschung A, vol. 37, no. 1, 74-77, (1982) CrossRef M. F. Al-Kadhemy, A. Al-Zuky, I. F. Al-Sharuee, "Theoretical Model to Study the Effect of Concentration and Impurities on the Fluorescence Spectrum of Fluorescein Solution in Ethanol using Fourier Series 3× 2", International Journal of Materials Physics, 2, 75-86, (2011). DirectLink D. V. Vezenov, B. T. Mayers, D. B. Wolfe, G. M. Whitesides, "Integrated fluorescent light source for optofluidic applications", Applied Physics Letters, volume 86, 041104, (2005) CrossRef V. P. Vladev, T. A. Eftimov, W. J. Bock, "Broad-band fluorescent all-fiber source based on microstructured optical fibers", Phot. Lett. Pol., vol. 7, no. 2, 41-43, (2015) CrossRef J. Żmojda, P. Miluski, M. Kochanowicz, J. Dorosz, A. Baranowska, M. Leśniak, D. Dorosz, "Luminescent properties of active optical fibers", Phot. Lett. Pol., vol. 11, CrossRef